PENETAPAN WALI ADLAL PADA PERKARA NOMOR 086/PDT.P/2013/PA.PBR DI PENGADILAN AGAMA PEKANBARU - Lestari Anggraeni; Mardalena Hanifah; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
One of human needs is marriage, because marriage is a requirement with respect to the physical and mental demands of a human being. Physical demands meant is sexual intercourse between men and women, while the spiritual demands in question is the creation of happiness because of affection between men and women. All of the above can be incorporated into a legal bond called Marriage. Based on Article 1 of Law No. 1 of 1974 About Marriage, hereinafter called the Marriage Act, the definition of marriage is the emotional and physical bond between a man and a woman as husband and wife with the intention of forming a family (household) were happy and everlasting based on God. To perform a marriage there must be harmony and conditions to be met, one of which is the guardian of marriage. If the marriage guardian adlal or reluctant to become guardian of marriage it is necessary to judge guardian. In this case relating to the Determination of Adlal Guardian No. 086/Pdt.P/2013/PA.Pbr in the Religious Court of Pekanbaru.The purpose of this thesis, namely: First, to know the basic consideration of Judge in determining the wali adlal in the Religious Court of Pekanbaru. Second, to determine the factors that led to the refusal to be a guardian of marriage for parents. This type of research can be classified in this type of sociological juridical research because in this study the authors directly conduct research on the location or point examined in order to provide a complete and clear picture of the issues examined.From the research results can be concluded. First, the judge in determining a guardian was adlal in case Number: 086/Pdt.P/2013/PA.Pbr is based on thorough consideration and comprehensive. Consideration of normative-juridical accordance with the legislation in force, namely Law No. 1 of 1974 About Marriage and the Compilation of Islamic Law which, in the case trustee adlal The Petitioner and her husband have fulfilled the terms of a marriage according to the laws and Islamic Shari'ah, and there is no prohibition/obstacles in implementing marriage. Second, the factors that led to the refusal to be a guardian of marriage for parents in case the mayor Determination Adlal with Number: 086/ Pdt.P/2013/PA.Pbr. Of guardians that the Applicant's father refused to be a guardian of marriage for prospective bridegroom less educated and work as a barber. Writer’s advice, first, it is expected that the judge in determining the adlal trustee determination not only create legal certainty, but also expediency and fairness as the highest legal ideals. Second, the guardian of marriage should not complicate the process of marriage for their daughters for reasons that do not conflict with Personality (religion), legislation and it should be still discussed and resolved amicably because marriage is a way of worship commanded by God glory to Him.Keywords: Marriage – Adlal guardian – Religious Court